Efficient quantification procedures for data evaluation of portable X-ray fluorescence – Potential improvements for Palaeolithic cave art knowledge. (December 2016) - Gay, M.; Müller, K.; Plassard, F.; Cleyet-Merle, J.-J.; Arias, P.; Ontañón, R.; Reiche, I.
Abstract: Portable x-ray fluorescence spectrometry (pXRF) has become fundamental in prehistoric research since it enables chemical studies that preserve the integrity of rock art or other investigated archaeological objects. This unique and fragile expression of our ancestors requires the use of non-invasive and non-destructive in situ analytical techniques. This provides significant sources of physicochemical information for enhancing the comprehension of the symbolic and ideological realm of past societies. Thus, XRF data acquired in the field allow giving more detailed insights into the pigment used by Palaeolithic artists, the rock art organisation inside the cave and the different frequentation periods of it. However, if the qualitative study is now well established and routinely used, quantitative evaluation encounters difficulties linked to the context of the study (karstic environment in our case) and the heterogeneous nature of the analysed material (nature of the pigments used, presence of several layers, conservation state of the rock art, type of the rock art support). Moreover, the non-invasive nature of this technique is faced with a large number of data since it offers the acquisition of statistically relevant data by multiple measurements of different spots on the same figure. The present work struggles with the issue of filling the gap of well-adapted quantitative procedures devoted to caves or rock-shelters analyses, and offers efficient tools and methodologies, which take into account the specificities of the studied rock art and its context. Additionally, the evaluation procedures of the high volume of data have to be effective. The analyses of drawings, monochrome and polychrome paintings of three Palaeolithic key cave sites, namely Rouffignac and Font-de-Gaume in Dordogne, Southern-France, and La Garma in Cantabria, Northern Spain, illustrate the new approaches and procedures developed in this study.